Whole serum as cell protection reagent in cell shipment at low or room temperature. (February 2023) - Liu, Daijiang; Fang, Dianliang; Li, Wen; Wan, Xiaoqiang; Lang, Lei; Wang, Zhenyan
Abstract: To maintain cell viability and characteristics physiological over long time or long-distance cell shipment is critical to promote the collaborative efforts in the research field of cell biology. Herein, we investigated the possibility of different concentration of fetal bovine serum as transport cell reagent. Cell suspension of three different mammalian cell lines were transported in 1.5 mL tube under different temperature conditions. Cell viability was closely related to environmental temperature and shipment time. No significant difference of cell survival rate was observed between 2–8 ℃ and 8–16 ℃ groups, under these two temperature conditions, reagent containing above 50 % FBS showed the best protection effect to maintain over 80 % cell survival rate. After 10 days of cell shipment under 2–16 ℃ environmental temperature, C3H10 cells exhibited the same multiple differentiation ability, 143B cells had the same capability of proliferation, migration and invasion, LX-2 cells showed the same activation state with TGF-β stimulation. Three cell lines maintained their primary characteristics after long time cell shipment. This entire shipment process does not require the maintenance of specific temperatures, humidity and container, providing a low-costing and convenient way for cell shipment between long distance laboratories. Highlights: Cell viability was closely related to environmental temperature and transport time during cell shipment. Cell transport reagent containing higher than 50 % FBS concentration could protect cell viability. Whole serum can be used as cell protection reagent in long time cell shipment under room temperature.